Development of a safety case for a closed tailings storage facility in the tropics - Thorp, J.; Herza, J. (Mine Closure 2024: Proceedings of the 17th International Conference on Mine Closure, 2024)
Owners of tailings storage facilities (TSFs) must meet their legal obligations and adhere to current industry practice in relation to tailings dam safety. In the common law frameworks, this involves demonstrating that the TSF risks are eliminated whenever reasonably practicable and, if not, are reduced so far as is reasonably practicable. A similar requirement to reduce risks to as low as reasonably practicable (ALARP) is included in the non-mandatory Global Industry Standard on Tailings Management (GISTM). Even in jurisdictions where legal and regulatory requirements do not explicitly mandate reducing risks so far as is reasonably practicable, and even if the owner does not adopt the GISTM, TSF owners should recognise that implementing practical risk controls aligns with current industry practice and thus falls within their duty of care. The safety case provides a platform for a structured and logical argument that all reasonably practicable risk controls are either in place or are planned for implementation, making it a valuable tool for TSF owners to demonstrate their commitment to minimising risks. This paper discusses the development of a safety case for a closed TSF with a permanent water cover in an equatorial tropical climate. The primary aims of the safety case were to outline plans for implementing reasonably practicable risk controls, address uncertainties that may necessitate additional controls in the future and demonstrate compliance with the GISTM.